Urban industrial relocation: The theory of edge cities - Francesca Medda; Peter Nijkamp; Piet Rietveld (European Regional Science Association (ERSA), 1998)
In recent years urban economists have focused their attention upon a 'newly recognized' phenomenon: edge cities. Such an urban growth pattern, although having its primary roots in the United States, can be an appropriate framework for examining European trends of urban industrial location. The objective of this study is to examine the relocation of firms from dominant industrial areas, for example, urban CBDs, to new locations at the urban outer boundaries. In this context, we develop in this paper a model based upon the theory of monopolistic competition ("Dixit and Stiglitz, 1977") that examines the economic relationships among firms at different locations. Such intra/inter relationships are examined from the point of view of complementarity. Complementarity in our case combines the two notions of firms' interaction with cumulative and reinforcing effects, and of coordination among firms in the local industrial organizations. Our interest in such a notion springs from the necessity to explain the spatial distribution of firms, particularly why firms in their location often choose to cluster. One of the explanations within the literature is that concentration in clusters is due to the need to share common infrastructures. However, this is just one of many possible explanations for this phenomenon. In our model, we will tackle this aspect of firm locations in clusters from the point of view of the elasticity of substitution. On the basis of the model we will formulate a policy framework regarding industrial suburbanization.
Keywords: 330